Orientasi Politik Panggulang Pada Pemilihan Kepala Desa Karama - Asriani; Nizar, Nizar (Universitas Muhammadiyah Sorong, 2023)
This research aims to find out and describe the orientation of the Pelgang in giving their right to vote in the Village Head Election in Karama. The type of research used is qualitative research with a descriptive type. The author determined the informants purposively. The author collected data through interviews and literature review. The results of the research show that Pelgang's political orientation in the election of the Karama Village Head is reflected in Cognitive Orientation, Affective Orientation and Evaluative Orientation.